Analysis of the Mouse Y Chromosome by Single-Molecule Sequencing With Y Chromosome Enrichment - Yano, Yuki; Chiba, Tomoki; Asahara, Hiroshi (Frontiers in Genetics, 2020)
Since human and mouse Y chromosomes contain repeated sequences, it is difficult to determine the precise sequences and analyze the function of individual Y chromosome genes. Therefore, the causes of many diseases and abnormalities related to Y chromosome genes, such as male infertility, remain unclear. In this study, to elucidate the mouse Y chromosome, we enriched the mouse Y chromosome using a fluorescence activated cell sorter (FACS) equipped with commonly used UV and blue 488 nm lasers and read the nucleotides using the Oxford Nanopore MinION long-read sequencer. This sequencing strategy allows us to cover the whole known region as well as the potential undetermined region of the Y chromosome. FACS-based chromosome enrichment and long-read sequencing are suitable for analysis of the Y chromosome sequences and may lead to further understanding of the physiological role of Y chromosome genes.